Pengaruh Inventory Intensity, Thin Capitalization, Capital Intensity, Research and Development dan Multinationality Terhadap Tax Aggressiveness pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2020-2022 - Lucky Bestian Febrianto; Rr. Tjahjaning Poerwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Thisi study aims to examined and analyzed the effect of Inventory Intensity, Thin Capitalization, Capital Intensity, Research and Development and Multinationality on Tax aggressiveness of manufacturing companies listed in the Indonesia Stock Exchange. The population of this research iis manufacturing companies ilisted in the Indonesia Stock Exchange (IDX) during the years 2020-2022. Samples are included in the criteria of thisi study were 335 companies using purposive samplingi method. This research datai analysis methods iusing thei multiple linear regressioni analysis. The results of the study indicate that the Thin Capitalization and Multinationality variable has a positive effect on Tax Aggressiveness. While Inventory Intensity, Capital Intensity and Research and Development do not affect Tax Aggressiveness.